Modelagem de processos erosivos em uma bacia agrícola: limitações e possibilidades - Didoné, Elizeu Jonas (2017)
The growing demand for modeling tools able represent erosive processes in catchments, and their connections, requires that mathematical modelling be associated with monitoring. This doctoral thesis sought to contribute to a description of the erosive processes at catchment scale, by combining monitoring and modeling techniques to reduce the impacts of agricultural activities in a large agricultural catchment through scenarios that simulate the impact of different conservation measures. Two studies were carried out in the Conceição River Catchment (800km2), a region characterized by the grain production system in the northwest of Rio Grande do Sul - Brazil. The first study sought to quantify the impact of different conservation measures on erosion and hydrosedimentological dynamics in a no-till agricultural catchment to simulate scenarios using the WATEM SEDEM model. Conservation measures reduced erosion and sediment yield in all scenarios. Crop leveling and terracing were the measures with greater impact in the reduction of the erosive process. The results demonstrate that soil losses due to erosion processes are significant and unsustainable in agricultural catchments in southern Brazil, and that soil erosion is exacerbated by the lack of information provided to the farmers and the use of isolated conservation measures without coordination at the catchment scale. The second study aimed to propose an efficient way to determine the current P factor through modeling, besides proposing conservation measures to better meet current practices. Four areas totaling 25 km2 were selected, representing the various properties present in the site. The efficiency of the current farming was determined by relating the angle between the sowing lines and the terrain level curves. In this study, values of P above 0.8 were obtained in over 60% of the area. This technique proved to be an important tool for determining factor P in a fast and spatialized way with potential for use in large areas, since an efficient determination of the P factor can result in a reduction of the erosion potential. In view of these results it is possible to affirm that conservation measures should not be isolated actions, but rather associated with other practices suitable for each type of land use. The use of mathematical models of erosion can be an important support tool in environmental management decision making and the methodology developed to determine the factor P in GIS can aid mathematical models to better simulate the impacts of conservation practices on erosive processes. Catchment scale modeling should be more widespread in Brazil in order to promote sustainable agricultural practices, reducing the anthropic impact on soil and water degradation. Farmers’ and local communities’ awareness should be raised to reduce soil degradation and sediment transfer to river systems.